2000
DOI: 10.1161/01.cir.101.6.631
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Loop Intra-Atrial Reentry in Humans

Abstract: Background-Dual-loop atrial reentrant tachycardias have not been clinically described. Methods and Results-Five patients (3 men, 2 women; mean age, 48Ϯ16 years) were studied 24Ϯ15 years after surgical closure of an ostium secundum atrial septal defect for drug-resistant atrial tachycardia. Complete tachycardia mapping was performed in the right atrium with multipolar catheters and a 3-dimensional electroanatomic mapping system (Biosense), followed by linear radiofrequency ablation of the narrowest part of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
96
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(102 citation statements)
references
References 17 publications
6
96
0
Order By: Relevance
“…7,8 Thus, there may be the complication of another loop reentry, together with typical AFL rotation around the TA. Furthermore, the other loop reentry would travel across the line between the SVC and IVC in the posterolateral wall of the RA, and this has been confirmed by conventional electrophysiological methods, 9 electroanatomic mapping 10 and, recently, by noncontact mapping. 7,8 The pattern of propagation across the posterolateral RA has been studied using virtual electrograms, 8 but the conduction patterns and conduction velocity (CV) across the CT during typical AFL, as seen on actual electrograms, are not completely understood.…”
mentioning
confidence: 75%
“…7,8 Thus, there may be the complication of another loop reentry, together with typical AFL rotation around the TA. Furthermore, the other loop reentry would travel across the line between the SVC and IVC in the posterolateral wall of the RA, and this has been confirmed by conventional electrophysiological methods, 9 electroanatomic mapping 10 and, recently, by noncontact mapping. 7,8 The pattern of propagation across the posterolateral RA has been studied using virtual electrograms, 8 but the conduction patterns and conduction velocity (CV) across the CT during typical AFL, as seen on actual electrograms, are not completely understood.…”
mentioning
confidence: 75%
“…[1][2][3][4][5][6][7] A recent study has reported that left atrial macroreentrant tachycardia (LAMRT) can be successfully abolished by radiofrequency (RF) linear lesion in most patients, 7 but the critical isthmus was not delineated in detail. The aims of this study were (1) to describe the electroanatomic characteristics of the reentry circuit in patients with LAMRT, (2) to assess the effect of RF lesions on the critical isthmus and the conduction block across the isthmus, and (3) to investigate atrial tachycardia recurrence in patients after successful ablation.…”
mentioning
confidence: 99%
“…The resulting arrhythmias are referred to as "lesion-related macrore-entrant ATs." 113,[172][173][174][175] Although CTI-dependent flutter is the most common underlying mechanism in these circumstances, it often coexists with incisional macro-re-entrant ATs, resulting in multiple re-entry circuits.…”
Section: Non-cavotricuspid Isthmus-dependent Atrial Fluttermentioning
confidence: 99%
“…Cavotricuspid isthmus-dependent flutter is common in patients with prior atrial surgery, and both CTI-and non-CTI-dependent macro-reentry circuits often coexist in a single patient. 173,[176][177][178][179][180] Successful ablation is dependent on identifying a critical portion of the re-entry circuit where it can be interrupted with either one or a line of RF applications.…”
Section: A Catheter Ablation and Mapping Of Non-cavotricuspid Isthmumentioning
confidence: 99%
See 1 more Smart Citation